PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nawianto, Syaifurridzal; Djazuli, Atim (Jurnal Management Risiko dan Keuangan, 2022)
The company's growth rate plays an important role in determining the high value of the company. This study aims to determine and analyze how much the influence of capital structure, profitability, and company growth have on the value of the automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2015 – 2019. This research is explanatory research with a quantitative approach. The data sources are financial reports from five automotive sub-sectors listed on the Indonesia Stock Exchange for the period 2015 – 2019. The data collection used in this study was carried out through the documentary method or documentation and literature study. The results show that hypothesis 1 shows that there is no significant effect between capital structure on firm value, hypothesis 2 shows that there is a significant influence between profitability on firm value, hypothesis 3 shows that there is no significant effect between firm growth on firm value, and hypothesis 4 shows that there is a simultaneous influence between capital structure, profitability and company growth on firm value.